Novel 3-methylindoline inhibitors of EZH2: Design, synthesis and SAR. Issue 2 (15th January 2017) - Ansari, Amantullah; Satalkar, Sharad; Patil, Varshavekumar; Shete, Amit S.; Kaur, Simranjeet; Gupta, Ashu; Singh, Siddhartha; Raja, Mohd.; Severance, Daniel L.; Bernales, Sebastián; Chakravarty, Sarvajit; Hung, David T.; et al.
Graphical abstract: Abstract: EZH2 (enhancer of zeste homologue 2) is the catalytic subunit of the polycomb repressive complex 2 (PRC2) that catalyzes the methylation of lysine 27 of histone H3 (H3K27). Dysregulation of EZH2 activity is associated with several human cancers and therefore EZH2 inhibition has emerged as a promising therapeutic target. Several small molecule EZH2 inhibitors with different chemotypes have been reported in the literature, many of which use a bicyclic heteroaryl core. Herein, we report the design and synthesis of EZH2 inhibitors containing an indoline core. Partial saturation of an indole to an indoline provided lead compounds with nanomolar activity against EZH2, while also improving solubility and oxidative metabolic stability.